2004
DOI: 10.1142/s0129626404001921
|View full text |Cite
|
Sign up to set email alerts
|

The Systolic Reconfigurable Mesh

Abstract: In this paper, we introduce the Systolic Reconfigurable Mesh (SRM), which combines aspects of the reconfigurable mesh with that of systolic arrays. Every processor controls a local switch that can be reconfigured during every clock cycle in order to control the physical connections between its four bi-directional bus lines. Data is input on one side of the systolic reconfigurable mesh and output from another side, one row/column per unit time. Efficient algorithms are presented for intermediate-level vision ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This chapter, demonstrated several techniques for forming graphs representing partial-order multiple-sequence alignment of a given set of N-aligned sequences, using two types of reconfigurable mesh architectures (the spin-wave version [10] and the VLSI version [11,12]). It showed that for a constant number of variables, the run-times of both architectures are the same, O(1).…”
Section: Discussionmentioning
confidence: 99%
“…This chapter, demonstrated several techniques for forming graphs representing partial-order multiple-sequence alignment of a given set of N-aligned sequences, using two types of reconfigurable mesh architectures (the spin-wave version [10] and the VLSI version [11,12]). It showed that for a constant number of variables, the run-times of both architectures are the same, O(1).…”
Section: Discussionmentioning
confidence: 99%
“…">IMAGE PROCESSING ALGORITHMSOver the past few decades, several mesh-based parallel architectures such as meshconnected computer, mesh-of-trees, pyramid, mesh with multiple buses, reconfigurable meshes, systolic meshes, and optical meshes have been considered for performing low and intermediate-level computer vision tasks [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The first section concentrates on image processing applications of nanoscale spin-wave architectures.…”
mentioning
confidence: 99%
“…In a systolic reconfigurable mesh (SRM), as described in [19], data is input into the reconfigurable mesh and eventually output from the other side, one column of data per unit of time. A systolic reconfigurable mesh (SRM) of size 16 is shown in Figure 19.1.…”
mentioning
confidence: 99%
See 2 more Smart Citations